Prinsip-Prinsp Utama Manajemen George R. Terry - Rifaldi Dwi Syahputra; Nuri Aslami (Pusat Riset dan Inovasi Nasional, 2023)
At this time, management has become one of the most important parts of daily life activities. Islam as a religion provides a deep ethical and moral framework, which can provide guidelines for the implementation of effective and fair management. According to George R. Terry, 1958 in his book Principles of Management (Organizing), Actuating (Implementation) and Controlling (Supervision). In achieving a goal, both in an organization and in a business, a management is needed which is carried out according to George R. Terry which is correlated based on an Islamic perspective with the aim of this research so that new values ​​emerge in managing and managing an organization or business so that it has a positive impact and efficiency in maintaining and running an organization or business based on an Islamic perspective. This research method uses qualitative research where this research is based on the literature of various literary books and scientific journals that strengthen the discussion of this research. The results of the research objective correlate with George R. Terry's model of leadership principles based on an Islamic perspective, with the hope of creating new values ​​in good leadership management based on Islamic Sharia, because in essence Islam brings people to the right path. follow the rules and stay away from the prohibitions of Allah SWT.